Shuttle run agility test in soccer athletes of under - 10 category with dry and wet conditions field - Tubagi Polito, L. F.; de Moura Carneiro, Y.; Moscaleski, L. A.; Figueira Junior, A. J.; Zanetti, M. C.; de Sá Pinto, C. G.; Dias1, H. M.; Nunes, H. M.; de Lima, S. I. (International Journal of Sports Science, 2017)
Introduction: The soccer is characterized by being the most practiced and known sport in the world, and has conquered new territories in recent years regardless of the characteristics of the practitioners. The performance of a soccer player can be understood by many factors, but the best indicator of overall performance of the athlete is agility. Such performance is related to psychosocial factors, which causes a certain difference between categories within the modality. Purposes: Identify the behavior of the agility variable in soccer athletes, at field with dry and wet conditions, through the application of the Shuttle Run Agility Test protocol. Methods: Participated of the study sixteen male soccer athletes in the Under-10 category of the Paulista Soccer Team with the following characteristics (height: 1.14 ± 0.07 m, body mass: 33.87 ± 5.14 kg, mass index Body weight: 17.2 ± 1.25 kg / m2). Results: The value obtained in the Shuttle Run tests in dry and wet field was 11.31 ± 0.34 sec and 11.42 ± 0.55 sec respectively. Conclusion: There was not significant difference between the Shuttle Run Agility Test performed in different environmental conditions (dry field and wet field). More studies are necessary to understand the behavior of soccer athletes about the divergence of environmental condition.